Development of a strategic management model to enhance the effectiveness of the cooperation between private companies and vocational colleges, China - Liu, Yanyan; Sermsri, Natchanun (Edelweiss Applied Science and Technology, 2025)
China’s transition from Made in China to “Created in China” underscores the urgency of effective school-enterprise cooperation to cultivate innovation-ready talent. Despite policy emphasis on industry-education integration, fragmented governance, misaligned incentives, and low enterprise engagement persist, reflecting gaps in both theory and practice. Grounded in stakeholder theory and collaborative governance frameworks, using a mixed-methods approach, data were collected from private enterprises and vocational colleges across diverse regions in China, employing a validated questionnaire to assess collaboration models, strategic alignment, and outcomes. The usable sample size was n=193 respondents. Furthermore, findings reveal that innovation-centric models, such as Industry-Academic-Research Integration, exert the strongest influence on partnership success, while strategic coherence defined as aligned objectives and adaptive governance emerges as a critical mediator between collaborative processes and outcomes. Modern apprenticeships demonstrate moderate efficacy, particularly in sectors with stable skill demands, whereas demographic factors show negligible impacts. The study’s novelty lies in its stratified, context-sensitive model, which diverges from rigid international frameworks by accommodating regional economic disparities and sectoral heterogeneities. By integrating institutional theory with practical governance mechanisms.